REPRESENTATION OF MURSI’S AND MILITARY’S SUPPORTERS IN KOMPAS AND REPUBLIKA NEWSPAPERS - NUFUS, HAYATUN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Representation, Critical Discourse Analysis (CDA), Systemic Functional Linguistic (SFL) The study of language use in newspaper has grown attention from many studies, including Critical Discourse Analysis (CDA). CDA explores the language practice used by newspaper which potentially produces bias. Transitivity analysis can be used as applicable and adequate tools in analysing discourse critically. The researcher conducts this study to know the non-neutral attitude in representing Mursi’s  and military’s supporters in Kompas and Republika news report. There are two problems to be solved in this study, namely : (1) How Mursi’s and Military’s supporters are represented through transivity process in Kompas and Republika?; (2) What is the meaning of different representation of Mursi’s and Military’s supporters constructed through transitivity process in news report of Kompas and Republika?.The  problems are analized using Systemic Functional Linguistic’s theory.This study uses qualitative approach that applies content or document analysis. Document analysis is used because the aim of this study is to describe the meaning and textual analysis of news report from Kompas and Republika. The data used in this study are 36 clauses from a news report of Kompas and 30 clauses from Republika’s containing transitivity processes.This study finds that  there are different representations Kompas news report has  cover tendency to give more support for military and less support for Mursi’s supporters. It also indicates intentional discrediting and denunciation of Mursi’s supporters. Different from Kompas, Republika has palpable tendency to give more support to Mursi’s supporter and indicates intentional discrediting and denunciation of military. Consequently, the reader can be positioned to participate in military’s action in Kompas whereas they are positioned to participate in Mursi’s supporters’ apprehension.The researcher suggests that the utilizing of critical thinking in CDA with the application of SFL should be more in time and activity thus it will be very useful and helpful for the students to do more. Besides, the next researchers can develop and explore the theory of CDA and SFL in different topics or objects by including the context. So, it will be very useful for rich studies of language especially in critical discourse analysis.